Director networks and informed traders - Akbas, Ferhat; Meschke, Felix; Wintoki, M. Babajide (Journal of Accounting and Economics, 2016)
We provide evidence that sophisticated investors like short sellers, option traders, and financial institutions are more informed when trading stocks of companies with more connected board members. For firms with large director networks, the annualized return difference between the highest and lowest quintile of informed trading ranges from 4% to 7.2% compared to the same return difference in firms with less connected directors. Sophisticated investors better predict outcomes of upcoming earnings surprises and firm-specific news sentiment for companies with more connected directors. Changes in board connectedness are positively associated with changes in measures of adverse selection.